Prediction of Cell-Penetrating Potential of Modified Peptides Containing Natural and Chemically Modified Residues - Kumar, Vinod; Agrawal, Piyush; Kumar, Rajesh; Bhalla, Sherry; Usmani, Salman Sadullah; Varshney, Grish C.; Raghava, Gajendra P. S. (Frontiers in Microbiology, 2018)
Designing drug delivery vehicles using cell-penetrating peptides is a hot area of research in the field of medicine. In the past, number of in silico methods have been developed for predicting cell penetrating property of peptides containing natural residues. In this study, first time attempt has been made to predict cell penetrating property of peptides containing natural and modified residues. The dataset used to develop prediction models, include structure and sequence of 732 chemically modified cell penetrating peptides and an equal number of non-cell penetrating peptides. We analyzed the structure of both class of peptides and observed that positive charge groups, atoms, and residues are preferred in cell-penetrating peptides. In this study, models were developed to predict cell penetration peptides from its tertiary structure using a wide range of descriptors (2D, 3D descriptors, and fingerprints). Random Forest model developed by using PaDEL descriptors (combination of 2D, 3D, and fingerprints) achieved maximum accuracy of 95.10%, MCC of 0.90 and AUROC of 0.99 on the main dataset. The performance of model also evaluated on validation/independent dataset and achieved AUROC of 0.98. In order to assist the scientific community, we have developed a web server "CellPPDMod” for predicting the cell-penetrating property of modified peptides (http://webs.iiitd.edu.in/raghava/cellppdmod/).